Strengthening the Role of Mosque Youth through a Community Religious Service Counseling Program at Al-Abror Mosque, South Sumatra: - - abdulgafur Haderom; Nurhasan; Fitriana; Apriyanti; Endang Switri (Universitas Muhammadiyah Palembang, 2026)
This community service program aims to strengthen the role of mosque youth in socio-religious services through community religious education at Al-Abror Mosque, South Sumatra. The activities were carried out through lectures, demonstrations, simulations, and direct mentoring. The materials specifically focused on funeral rites management. The results showed an improvement in the participants’ understanding, practical skills, and motivation to become more actively involved in mosque activities. This can be seen from the pre-test score of 49.7 and the post-test score of 84.7. In addition, the program had a positive impact on the character development of the youth, such as fostering responsibility, social awareness, and teamwork. Overall, this program proved effective in strengthening the capacity of mosque youth as agents of change in the religious and social life of the community.